2020
DOI: 10.1016/j.lfs.2020.117842
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between endoplasmic reticulum stress and anti-viral activities: A novel therapeutic target for COVID-19

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 85 publications
(98 reference statements)
2
81
0
Order By: Relevance
“…Changing the administration route might increase the bioavailability of a compound. For example, the bioavailability of an anti-inflammatory compound, andrographolide, is increased when it is administered intravenously instead of through oral administration ( 295 ). Other methods to enhance the bioavailability of target compound include using drug delivery systems, the nano-formulation of a drug, using adjuvant systems, or altering structural analogs ( 220 , 296 ).…”
Section: Drug Discovery From Psms: Addressing the Major Challenges Tomentioning
confidence: 99%
“…Changing the administration route might increase the bioavailability of a compound. For example, the bioavailability of an anti-inflammatory compound, andrographolide, is increased when it is administered intravenously instead of through oral administration ( 295 ). Other methods to enhance the bioavailability of target compound include using drug delivery systems, the nano-formulation of a drug, using adjuvant systems, or altering structural analogs ( 220 , 296 ).…”
Section: Drug Discovery From Psms: Addressing the Major Challenges Tomentioning
confidence: 99%
“…Melatonin is a naturally occurring molecule assumed to be present in every species [ 19 ]. Due to its antioxidant, anti-inflammatory, as well as other properties [ 20 , 21 , 22 , 23 , 24 , 25 ], it has been speculated to be a promising molecule for treating COVID-19 patients [ 18 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], and also other deadly viral infectious diseases [ 48 , 49 , 50 , 51 ]. A small scale clinical trial has also shown promising results [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, we posit that new vulnerabilities in the regulatory and metabolic networks of a virus-infected cell can be targeted with drugs that will have no cytotoxicity to uninfected cells. Common transcriptional responses of virally infected cells include innate immune responses as well as cellular stress responses such as the unfolded protein response, which may suggest specific targets for host-directed antivirals that can be designed to either selectively disable infected cells or support antiviral activity of the innate cellular, and perhaps the coupled adaptive immune, response to infection (Banerjee et al, 2020;Ferreira et al, 2020;Netea et al, 2020).…”
Section: Mast Et Almentioning
confidence: 99%